Catalytic and Thermal Cracking of Bio-Oil from Oil-Palm Empty Fruit Bunches, in Batch Reactor - Santiyo Wibowo; Lisna Efiyanti; Gustan Pari (Universitas Gadjah Mada, 2020)
The world’s potency of fossil-derived petroleum fuels has declined steadily, while its consumption continues to rise ominously. Therefore, several countries have started to develop renewable fuels like bio-oil from biomass. Relevantly, the aim of this research was to explore the technical feasibility of upgrading the qualities of crude bio-oil (CBO) produced from the pyrolysis on oil-palm empty fruit bunches (OPEFB) using Ni/NZA catalyst in a batch reactor. The natural zeolite (NZ) was activated by HCL 6 N and NH4Cl (obtained sample NZA). Supporting Ni onto NZA was conducted with an impregnation method using a salt precursor of Ni(NO3)2·6H2O followed by calcination with a temperature of 500 °C. Catalyst characterization includes determining the site of TO4 (T = Si or Al) in zeolites, acidity, crystallinity, and catalyst morphology. Cracking reaction of CBO was carried out in batch reactor in varied temperatures of 250 and 300 °C with the variation of catalyst weight of 0, 4, 6, and 8% toward CBO. Several analyses of the liquid product such as product yield, specific gravity, pH, viscosity, calorific value, and chemical compound were conducted. The results showed that acidification and Ni loading on zeolite samples increased their acidity. The optimum CBO’s cracking condition was judged to be the temperature of 300 °C with 6% Ni/NZA catalyst use, whereby the fuel yield reached 26.42% and dominated by particular compounds comprising phenol, octanoic acid, and alkane hydrocarbons. Under such conditions, the characteristics of fuel were pH 3.54, specific gravity 0.995, viscosity 14.3 cSt, and calorific value 30.85 MJ/kg.